Employee well-being evaluation and proposal of activities to increase the level of health's area: The Czech case - Petra Horváthová; Kateřina Kashi; Hana Štverková; Marie Mikušová (Administrative Sciences, 2021)
Well-being and its evaluation, is currently considered one of the key trends in the practice of companies in the world and in the Czech Republic. Research in the field of well-being confirms that there is a positive correlation between a company's well-being and the company's performance. Satisfied and healthy employees contribute to the prosperity of the company through their higher work productivity and efficiency, and indirectly, through reduced incapacity for work and presenteeism. The purpose of this paper is to evaluate the employees' well-being of a specific company in the Czech Republic and propose activities for increasing the level of the most problematic of five areas of employees' well-being. The authors formulated two research questions and two hypotheses. Research questions were answered on the basis of the evaluation of an online questionnaire survey among 463 production staff of the company, hypotheses were statistically confirmed. The main results of this article include the identification of the most problematic area of well-being - the area of health - as well as the proposal of specific activities to improve the level of this area, the introduction which should achieve higher level of employees work productivity. The benefits of well-being show that companies should pay attention to it.
Keywords: 350; activities; career; Czech Republic; evaluation; financial; health and community area; production staff; social; well-being